Strategi Penegakan Disiplin Aparatur Sipil Negara Pada Dinas Perumahan Dan Kawasan Permukiman (DPKP) Kota Serang - Rida Astuti Pratiwi; Ita Rosita Wahyiah; Luis Fiska Rahayu; Malik Fatoni; Mohamad Ikrom Arasid (Journal of Innovative and Creativity, 2025)
This research aims to describe the disciplinary enforcement strategies for Civil Servants (ASN) at the Department of Housing and Settlement Areas (DPKP) in Serang City, analyze the effectiveness of the preventive, corrective, persuasive, and repressive approaches applied, and identify supporting and inhibiting factors in its implementation. This study uses a descriptive qualitative approach with data collected through observation, in-depth interviews with seven informants, and documentation studies. The results show that the disciplinary enforcement strategy at DPKP Serang City refers to the four approaches formulated by Nawawi’s theory, but its implementation is not yet optimal. The preventive approach is not fully internalized, the corrective approach is often inconsistent, the persuasive approach lacks a formal reward system, and the repressive approach is hindered by bureaucratic procedures. Supporting factors such as exemplary leadership and the use of digital attendance systems help promote discipline, while obstacles include tolerance of minor violations, a weak reward system, and the lack of continuous training. This research recommends improving the disciplinary system by strengthening the role of leaders as role models, renewing disciplinary policies, and implementing a fair and consistent reward and punishment system to foster a sustainable culture of discipline.